Assessment of the feed additive consisting of Pediococcus acidilactici NCIMB 30005 for all animal species for the renewal of its authorisation (Microferm ltd.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of the authorisation of a preparation of Pediococcus acidilactici NCIMB 30005 as technological additive to improve ensiling of fresh material for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There was no new evidence that would lead the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) to reconsider its previous conclusions for all animal species, consumers and the environment, for which the additive is considered to remain safe. Regarding the user safety, the Panel concluded that the additive should be considered a skin and respiratory sensitiser, and any exposure through the skin and respiratory tract is considered a risk. In the absence of data, no conclusion could be drawn on the eye irritation potential of the additive. There is no need for assessing the efficacy of the additive in the context of renewal of the authorisation.